Total skin self-examination at home for people treated for cutaneous melanoma: development and pilot of a digital intervention. Issue 8 (6th August 2015) - Murchie, Peter; Allan, Julia L; Brant, William; Dennis, Matthew; Hall, Susan; Masthoff, Judith; Walter, Fiona M; Johnston, Marie
Abstract : Objectives: To develop a digital intervention to prompt, support, and respond to the outcomes of total skin self-examinations (TSSEs) at home by people treated for cutaneous melanoma. Design: A complex intervention development study. Setting: Northeast Scotland. Participants: Semistructured scoping interviews; people previously treated for cutaneous melanoma (n=21). Pilot testing: people treated for melanoma stages 0–2C (n=20); general practitioners (n=6); and a nurse specialist in dermatology (n=1). Intervention: A tablet-based digital intervention designed to prompt and support TSSEs comprising instructional videos and electronic reporting (including photographs) to a clinical nurse specialist in dermatology, with subsequent clinical triage. Primary and secondary outcome measures: Qualitative assessment of intervention feasibility and acceptability, and quantitative assessment of intentions and confidence to perform TSSEs in pilot participants. Results: The majority of pilot participants were strongly positive and adhered well to the intervention (n=15), with 7 of these reporting symptoms of concern at some point during the 6-month pilot. 4 patients complied intermittently, 3 reporting skin problems at least once during the pilot, and 1 withdrew. 2 patients underwent skin surgery as a result of participating in the pilot, with 1 diagnosed as having a recurrent melanoma and the other, a benign lesion. A number of practical issues to improve the usability of the intervention were identified. The proportion of participants reporting intention to check their skin at least monthly increased during the intervention as did confidence to conduct a skin check. Conclusions: People previously treated for cutaneous melanoma are prepared to use digital technology to support them in conducting TSSE. An intervention has been developed which is practical, effective and safe, and after addressing minor practical issues, could now be evaluated for clinical outcomes in a randomised clinical trial.